IMPACTS OF COMPUTERISED MANAGEMENT PROCESS OF STOCKS IN MINEIRAS FAMILY FIRMS OF BUILDING MATERIAL: MULTICASES STUDY - Jones, Graciela Dias Coelho; Ramos da Silva, Vanessa (European Scientific Journal, ESJ, 2013)
The growth in civil construction in Brazil in recent years has generated many opportunities for the market. Entrepreneurs have sought solutions that help them in decision making in order stay competitive and market construction materials. This study aims to analyze the impacts of the process of computerised inventory management in mineiras family firms of building materials, located in Uberlândia in Minas Gerais state, Brasil. This is a qualitative work. For its development, we adopted the multicases study, with the completion of interviews and participant observation, in order to know the process studied. The result was that the management of stock in the company not computerized presented some advantages like the fact not depend on external factors such as power supply or internet connection for consultation or low registration of products in stock. It is noteworthy, however, that there are numerous benefits of information system for companies that make use of it. It was observed that the information system allows users to inventory control through reporting, query faster gifts of items in stock, facilitating the activities of control incoming and outgoing products, management and analysis of items sold, among other advantages.